Analysis of Hysterotomy Extension at Unscheduled Cesarean Delivery - Bunn, Jason G.; Tang, Albert; Warncke, Kristen; Gilazgi, Saron; Mcintire, Donald D.; Nelson, David B.; Spong, Catherine Y.; Hawkins, J. Seth (American Journal of Perinatology, 2025)
This study aimed to determine if the rate of hysterotomy extensions increases with increasing cervical dilation in unscheduled cesarean deliveries, and to develop a measure of the severity of hysterotomy extension for quantifying morbidity.This is a retrospective study of unscheduled cesarean deliveries relating to labor dystocia and/or nonreassuring tracings from January 1, 2021, to December 31, 2021. Severe extension was defined as bilateral or adjacent to a structure such as the uterine artery, broad ligament, or cervix, and was compared with uterine artery extensions alone.There were 990 unscheduled cesarean deliveries included. Extensions (n = 233) significantly increased with increasing cervical dilation (p < 0.0001), complicating more than 30 and 50% at 6 and 10 cm of cervical dilation, respectively. Apart from this trend, a logistic regression analysis indicated cervical dilation was an independent risk factor for extension. Transfusions of at least 2 units of blood were five times (26 vs. 5%) more likely for patients with severe extensions than no extension (p < 0.0001).Hysterotomy extensions significantly increase with increasing cervical dilation, and cervical dilation is an independent risk factor for extension. A composite measure of severity accounts for different types of extension when quantifying morbidity, but uterine artery extension is the primary driver of maternal morbidity in cases without hysterectomy.
Keywords: cesarean morbidity; hysterotomy extension; labor dystocia; second stage arrest